Love Your Resource Neighbor A Guide to Resource Collaboration in Head Start. - Chapel Hill Training-Outreach Project, NC.; Chapel Hill Training-Outreach Project, NC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
A product of a May 1976 conference on Head Start's collaboration with other agencies, the guide presents information on providing services to preschool handicapped children and their families. The first section discusses the development of the Kentucky State Advisory Council to Head Start's Program for Exceptional Children. Reviewed in the second section are screening procedures used by the state of North Carolina. The rationale, planning, training activities, personnel roles, implementation, evaluation, and followup of the screening are analyzed. The final section discusses the planning involved in holding a conference on prevention and early intervention with developmental disabilities in Owensboro, Kentucky. Considered are such elements as scheduling, advertising and promotion, and planning. Also included in the document are scripts from three slide/tape shows on agency collaboration. (CL)
Sponsoring Agency: Office of Child Development (DHEW), Washington, DC.
Educational level discussed: Preschool Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Role; Community Organizations; Conferences; Handicapped Children; Preschool Education; Prevention; Public Agencies; Screening Tests; State Agencies; Project Head Start; Guides, General